2014
DOI: 10.1007/s00213-014-3650-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition

Abstract: The significant relations observed in the current study between TNFα and the PANSS and its subscales suggest that immune disturbance may be involved in the psychopathology and cognitive deficits of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 57 publications
7
43
1
Order By: Relevance
“…The roles of TNF-α in controlling neuronal excitability and metabolisms of glutamate, dopamine, and serotonin neurotransmitters make it an outstanding candidate for etiology and pathophysiology of schizophrenia (Tian et al, 2014). Alterations in serum TNF-α level in chronic schizophrenia patients have been reported previously, but with inconsistent results, being no different (Pedrini et al, 2012; Kunz et al, 2011), elevated (Lin et al, 1998; Naudin et al, 1997; Beumer et al, 2012; García-Miss et al, 2010; Luo et al, 2014) or reduced (Francesconi et al, 2011; Lv et al, 2014; Potvin et al, 2008), as compared with healthy control subjects. Nonetheless, these evidences implicate the role of TNF-α and TNF-α-related signaling pathways in the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The roles of TNF-α in controlling neuronal excitability and metabolisms of glutamate, dopamine, and serotonin neurotransmitters make it an outstanding candidate for etiology and pathophysiology of schizophrenia (Tian et al, 2014). Alterations in serum TNF-α level in chronic schizophrenia patients have been reported previously, but with inconsistent results, being no different (Pedrini et al, 2012; Kunz et al, 2011), elevated (Lin et al, 1998; Naudin et al, 1997; Beumer et al, 2012; García-Miss et al, 2010; Luo et al, 2014) or reduced (Francesconi et al, 2011; Lv et al, 2014; Potvin et al, 2008), as compared with healthy control subjects. Nonetheless, these evidences implicate the role of TNF-α and TNF-α-related signaling pathways in the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, we found that serum TNF-α level was significantly lower in chronic ketamine users (p < 0.05) and serum TNF-α level showed a significant negative association with PANSS total score and negative subscore (p < 0.01). Recent studies have shown that decreased serum TNF-α level in chronic schizophrenia patients was significantly negatively correlated with PANSS total score and positive subscore (Lv et al, 2014; Potvin et al, 2008), suggesting patients with lowered TNF-α levels would be more likely to have severer psychopathological symptoms. The negative correlation TNF-α level with the severity of psychopathological symptoms may seem contradictory to what proinflammatory cytokines are generally recognized as worsening factors for the pathology of psychiatric disorders at the first glance.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it should be noted that our sample size was limited; however, it is one of the largest studies analyzing serum cytokine levels with respect to cognitive functioning in schizophrenia 50,54,55,76. Secondly, all our patients were medicated, while the association of TGF-β level with cognitive functioning in unmedicated first-episode schizophrenia patients would be much more reliable.…”
Section: Discussionmentioning
confidence: 99%
“…There is a trend towards TNF-α increase in SZ. One study showed lower levels of TNF-α in SZ subjects than in controls, demonstrating that we need to better understand the biological mechanisms in SZ to produce stronger evidence [40]. Therefore, chronic SZ patients on antipsychotics might show no cytokine differences when compared to HC or their respective SB [41].…”
Section: Discussionmentioning
confidence: 99%